The Duration of Medicaid Spells: An Analysis Using Flow and Stock Samples - Berger, Mark C.; Black, Dan A. (The Review of Economics and Statistics, 1998)
We use unique data from the Medicaid program of the Commonwealth of Kentucky to examine the duration of Medicaid spells. The data set consists of a one-in-ten sample of all Medicaid recipients in Kentucky on July 1, 1986, and a similar sample of all new spells between July 1, 1986, and June 30, 1987. Because the beginning date of Medicaid recipiency is known for all spells, this mixed "stock" and "flow" sample allows us to identify the duration of Medicaid spells for up to twenty years. This is in contrast to other studies using short panels of new spells. We find significant differences in hazard functions across program eligibility categories, suggesting that the cost of expanding Medicaid or the savings from contracting it would vary depending on the eligibility group affected by the change in policy. © 1998 by the President and Fellows of Harvard College and the Massachusetts Institute of Technolog